Uji Komparasi Pengaruh Good Corporate Governance, Capital Intensity, dan Kepemilikan Asing Terhadap Penghindaran Pajak Pada Bursa Efek Indonesia dan Bursa Efek Filipina - Sugeng Hariadi; Venantia Finny Ayuny Putri; Dyah Aruning Puspita (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The goal of this research was to examine the various ways that capital intensity, foreign ownership, and good corporate governance (GCG) affect tax evasion on the Indonesian and Philippine stock exchanges. Data from the property and real estate sectors of the Indonesia Stock Exchange and the Philippine Stock Exchange, Inc. in 2021–2023 were used in this research. Multiple linear regression analysis is the analytical method employed in this study, along with the independent sample t-test as a hypothesis test. According to the findings, there were variations in tax avoidance between institutional ownership, audit committee, audit quality, capital intensity, and foreign ownership.